RetroWoT: A Method to Integrate Brownfield Devices in the Web of Things - Dorsch, Rene; Freund, Michael; Ascencion Arevalo, Kiara Marnitt; Harth, Andreas (IoT 2024 - Proceedings of the 14th International Conference on the Internet of Things, 2025)
We present RetroWoT, an approach that automates the integration of brownfield Internet of Things (IoT) devices into the Web of Things (WoT). RetroWoT composes Thing Descriptions (TDs) as interface description specifications for the WoT from device-specific information. For the generation of TDs, our approach leverages discovery methods within IoT networks for device-information gathering, Semantic Web technologies for information alignment across IoT protocols, and service specifications from IoT standards developing organizations (SDOs) to increase semantic richness. We evaluated our approach’s validity and performance through empirical studies and an implementation of the ZigBee and Bluetooth Low Energy (BLE) IoT protocols. Our experiments show that RetroWoT enables the generation of TDs for all ZigBee and service discovery enabled BLE-based devices. Enriching a TD with services from the Bluetooth and ZigBee SDOs improves the descriptive richness in up to 73% of all services in our experiment. Furthermore, our analysis of RetroWoT’s implementation shows that the method scales linearly with the number of services provided by an IoT device and generates a TD within 7 seconds on average per device. With this approach, we support the adoption of the Web of Things by facilitating the creation, combination, and exploration of large-scale Web of Things-based systems.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Integration; Internet of Things; Web of Things